Parliamentary Activity from June to December (XIII Legislature) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
The purpose of monitoring the parliamentary activity carried out in the Madrid Assembly, the subject of this parliamentary chronicle, is to offer information related to the second session of the XIII Legislature, which runs from January to June, 2024.
Keywords: Parliamentary activity